PENGEMBANGAN UKS (UNIT KESEHATAN SEKOLAH) DENGAN IMPLEMENTASI SENAM DISMENOREA TAHUN 2021 - Ingka Kristina Pangaribuan; Marlina Simbolon; Dewi Sartika; Selfi Indah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
DEVELOPMENT OF UKS (SCHOOL HEALTH UNIT) WITH IMPLEMENTATION OF DYMENOROREAL GYSMS Ingka Kristina¬¬¬¬1, Marlina Simbolon¬¬¬¬2, Dewi Sartika¬¬¬¬2 Beautiful Selfies¬¬¬¬2HUSADA MEDAN PARTNER STIKES1STIKes Mitra Husada Medan2STIKes Mitra Husada Medan3STIKes Mitra Husada Medan ingka.kristina@gmail.com, Simbolon.marlina@yahoo.com,dewisartika2226@gmail.com,selvyindah555@gmail.com ABSTRACT Adolescents are individuals who when viewed physically are experiencing development and psychologically are experiencing emotional development, so that youth are human resources for development both now and in the future. As a candidate for the next generation who will replace the previous generation. Internationally, WHO refers to "young people" with an age limit of 10-24 years, while those aged 10-19 years are called "adolescenta" or teenagers. Adolescents face a period of social and cultural change.Dysmenorrhea is pain in the abdomen that comes from uterine muscle cramps and occurs during menstruation without signs of infection or pelvic disease. The intensity of dysmenorrhea can decrease after pregnancy or around the age of 30 years. Dysmenorrhea exercise is a relaxation technique. Exercise or physical exercise can produce endorphins. This hormone can function as a natural sedative produced by the brain which gives birth to a sense of comfort and to reduce pain during contractions.The research design used a quasi-experimental method (Quasi Experiment) with a one group pre-post test design. The sample in this study were teenagers at SMA TRISAKTI Medan, North Sumatra Province, as many as 113 teenagers using the Simple Random Sampling Technique on adolescents who experienced dysmenorrhea.The results of the univariate data show that the majority of teenage girls in class XII are 108 students (34.7) and the minority in class X are 100 (33%) and the majority respondents are moderate pain as many as 53 students (46.9) and the minority with severe pain are as many as 22 (19.5%). The results of the bivariate test using the Wilxocon test to determine the difference in the average menstrual pain with a value (p-value = 0.000), namely that there is an effect of dysmenorrhoea exercise in UKS (School Health Unit). This dysmenorrhea exercise is a complementary therapy that can be used by health facilities and the community to reduce menstrual pain and reduce the use of painkillers. Keywords: Gymnastics Dysmenorrhea, Menstrual Pain (Dysmenorrhea)